Afghanistan morass: An analysis of Pakistan’s security after NATO withdrawal - Iqra Jathol (Journal of Political Studies, 2023)
The study discusses about the emerging security challenges to Pakistan after NATO withdrawal from Afghanistan and Re-emergence of Taliban. After 19 years US signs an agreement and leaves Afghanistan in 2021. After withdrawal of NATO forces from Afghanistan, country faces alarming security concerns due to extreme hunger and poverty. To understand Pakistan's security dilemma, it is essential to analyze the Afghanistan’s current security scenario under the Talban government, foreign intervention in Afghanistan, Humanitarian crises, Pak-afghan relation, boarder issue, the movements in Pakistan and refugee crises, and then assess the security concerns of Pakistan due to Afghanistan crises after US withdrawal. Certainly, the Indian factor cannot be discounted during the study of Pakistan's security dilemma or south Asian security environment. The study is in qualitative mode and tries to find some security solutions through the lens current condition of Afghanistan.